Choosing the Right Life Partner: Ecological Drivers of Lichen Symbiosis - Vančurová, Lucie; Malíček, Jiří; Steinová, Jana; Škaloud, Pavel (Frontiers in Microbiology, 2021)
Lichens are an iconic example of symbiotic systems whose ecology is shaped by the requirements of the symbionts. Previous studies suggest that fungal (mycobionts), as well as photosynthesizing (phycobionts or cyanobionts) partners have a specific range of acceptable symbionts that can be chosen according to specific environmental conditions. This study aimed to investigate the effects of climatic conditions and mycobiont identity on phycobiont distribution within the lichen genera Stereocaulon, Cladonia, and Lepraria. The study area comprised the Canary Islands, Madeira, Sicily, and the Aeolian Islands, spanning a wide range of climatic conditions. These islands are known for their unique and diverse fauna and flora; however, lichen phycobionts have remained unstudied in most of these areas. In total, we genetically analyzed 339 lichen samples. The phycobiont pool differed significantly from that outside the studied area. Asterochloris mediterranea was identified as the most abundant phycobiont. However, its distribution was limited by climatic constraints. Other species of Asterochloris and representatives of the genera Chloroidium, Vulcanochloris, and Myrmecia were also recovered as phycobionts. The selection of symbiotic partners from the local phycobiont pool was driven by mycobiont specificity (i.e., the taxonomic range of acceptable partners) and the environmental conditions, mainly temperature. Interestingly, the dominant fungal species responded differently in their selection of algal symbionts along the environmental gradients. Cladonia rangiformis associated with its phycobiont A. mediterranea in a broader range of temperatures than Stereocaulon azoreum, which favors other Asterochloris species along most of the temperature gradient. S. vesuvianum associated with Chloroidium spp., which also differed in their temperature optima.